Prevalence of Urine Glucose-Associated Bacteriuria in Diabetics and Antibiotic Susceptibility Patterns of the Isolated Bacteria. (Tanzania Medical Journal, 2008)
Objectives: This study aimed at determining the influence of urine glucose on prevalence of bacteriuria in diabetic patients and to carry out antibiotic susceptibility patterns testing on the isolated bacteria. Methods: This is cross-sectional study conducted at Diabetes Clinic-Muhimbili National Hospital, by collecting 133 midstream urine (MSU) specimens from 133 patients who were attending the clinic during the study period. The MSU specimens were then cultured on cystine lactose electrolyte deficient (CLED) agar medium using the standard wire loop technique. The isolated microorganisms were identified and microbial counts determined by using conventional methods. Urine glucose levels (UGLs) were determined using urinalysis reagent strips (Acon Laboratory Inc., USA). Results were interpreted and classified as negative, trace, positive (+), positive (++) or positive (+++). Antibiotic susceptibility patterns of the isolated bacteria were conducted using disk-diffusion method in accordance with National Committee on Clinical Laboratory Standards (NCCLS) guidelines. Checklists of clinical histories were also used for collection of complementary data on the patient weight and age. All the obtained data were coded and entered in computer and then analyzed using computer software SPSS version 10. Results: Majority of the patients 118(88.7%) manifested no significant bacterial growth (NSBG). Out of the patients who manifested NSBG, majority (73%) had no/negative urine glucose levels (UGLs). Escherichia coli were the most frequently isolated microorganism (18.8%), which were also the most predominantly isolated microorganisms from patients with negative urine glucose levels. Klebsiella spp and Pseudomonas aeruginosa were found in all patients with glycosuria. More females (12%) manifested higher UGLs in comparison to males' counterpart (7.5%), which coincided with the higher bacterial counts in female diabetics. All the isolated microorganisms were found to be susceptible to nalidixic acid (30µg). Nevertheless, all the microorganisms were resistant to ampicillins (10µg), flucloxacillin (10µg) and tetracycline (30µg) with exception of E. coli which was susceptible to the latter drug. Conclusion: The study revealed that E. coli was the most frequently isolated microorganisms (18.8%) and bacteriuria was relatively more prevalent in female patients (25%) compared to males (16%). Notwithstanding, majority of the patients (88.7%) manifested NSBG. Direct correlation between bacteriuria and UGLs was observed though its relation is still unclear. The antibiotic resistances identified make it necessary for antibiotic susceptibility testing to be carried out prior antibiotic prescription. Tanzania Medical Journal Vol. 23 (1) 2008: pp. 16-19